2004
DOI: 10.1152/ajplung.00240.2004
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α-induced TRPC1 expression amplifies store-operated Ca2+influx and endothelial permeability

Abstract: influx in response to thrombin exposure. We observed that thrombininduced Ca 2ϩ influx in TNF-␣-stimulated HPAEC was twofold greater than in control cells. To address the relationship between store-operated Ca 2ϩ influx and TRPC1 expression, we overexpressed TRPC1 by three-to fourfold in the human dermal microvascular endothelial cell line (HMEC) using the TRPC1 cDNA. Thrombininduced store Ca 2ϩ depletion in these cells caused approximately twofold greater increase in Ca 2ϩ influx than in control cells. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(161 citation statements)
references
References 42 publications
3
152
1
1
Order By: Relevance
“…We have shown that SOCE induced by thrombin ligation of PAR-1 mediates vascular barrier dysfunction and amplifies the expression of inflammatory genes in endothelial cells (3,15,16,32,33). Recent studies have shown that STIM1 is crucial for the activation of SOCE in endothelial cells (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that SOCE induced by thrombin ligation of PAR-1 mediates vascular barrier dysfunction and amplifies the expression of inflammatory genes in endothelial cells (3,15,16,32,33). Recent studies have shown that STIM1 is crucial for the activation of SOCE in endothelial cells (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TRPC1-gated Ca 2+ entry is capable of stimulating nuclear factor (NF)-κB via AMP-activated protein kinase and PKCδ, so that NF-κB may initiate the transcriptional programme involved in the host defense to inflammatory stimuli and in EC resistance to apoptosis [219,220] . NF-κB, in turn, increases TRPC1 expression in ΤΝF-α-stimulated cells, thus establishing a feed-forward loop that amplifies agonist-elicited SOCE and the increase in transendothelial permeability [221,222] . Similarly, AngII upregulates TRPC1 levels in an NF-κB-dependent manner in ECs [223] .…”
Section: +(Wb Ihc) +(Wb Ihc) +(Wb Ihc)mentioning
confidence: 99%
“…34 Since caveolin-1, which has a similar overall structure to caveolin-3, 35 is known to bind TRPC1 in smooth muscle cells 36 this could mean that by having increased caveolin-3 expression in dystrophic muscle, TRPC1 expression might also be greater.I nf act, there is a suggestion from Western blots that TRPC1 levels are increased in mdx muscle compared to wild-type, 28 although this point was not specifically raised by the authors of this paper.F urthermore, recent work from our laboratory has shown that TRPC1 levels are greater in cardiac muscle from old mdx mice compared to wild-type (Williams & Allen, unpublished observations). In relation to this idea, it has recently been shown in endothelial cells that TRPC1 expression can be increased by the proinflammatory cytokine, tumour necrosis factor (TNFα), 37 which is intriguing in light of the fact that the levels of TNFα are enhanced in mdx muscle. 38 Afi nal point of interest is that caveolin-3 interacts with β-dystroglycan, to which dystrophin normally binds, and is thought to compete with dystrophin for this binding site.…”
Section: Ion Channelsmentioning
confidence: 99%